Galactomannan antigen as one of the markers for the diagnosis of invasive aspergillosis - O.O. Yastremska (Danylo Halytsky Lviv National Medical University, 2019)
The article deals with the state of the early clinical and laboratory diagnostics problem of invasive form of aspergillosis.